NECA alleviates inflammatory responses in diabetic retinopathy through dendritic cell toll-like receptor signaling pathway - Li, Lanjiao; Chen, Jichun; Wang, Zhenyan; Xu, Yan; Yao, Hao; Lei, Wulong; Zhou, Xiyuan; Zheng, Minming (Frontiers in Immunology, 2024)
Introduction This study examined the impact of 5’-(N- ethylcarboxamido)adenosine (NECA) in the peripheral blood of healthy individuals, those with diabetes mellitus, diabetic retinopathy (DR), and C57BL/6 mice, both in vivo and in vitro. Methods Enzyme-linked immunosorbent assay (ELISA) and flow cytometry (FCM) were used to evaluate the effects of NECA on dendritic cells (DCs) and mouse bone marrow-derived dendritic cells (BMDCs) and the effects of NECA-treated DCs on Treg and Th17 cells. The effect of NECA on the Toll-like receptor (TLR) pathway in DCs was evaluated using polymerase chain reaction (PCR) and western blotting (WB). Results FCM and ELISA showed that NECA inhibited the expression of surface markers of DCs and BMDCs, increased anti-inflammatory cytokines and decreased proinflammatory cytokines. PCR and WB showed that NCEA decreased mRNA transcription and protein expression in the TLR-4-MyD88-NF-kβ pathway in DCs and BMDCs. The DR severity in streptozocin (STZ) induced diabetic mice was alleviated. NECA-treated DCs and BMDCs were co-cultivated with CD4+T cells, resulting in modulation of Treg and Th17 differentiation, along with cytokine secretion alterations. Conclusion NECA could impair DCs’ ability to present antigens and mitigate the inflammatory response, thereby alleviating the severity of DR.